Optimizing COVID-19 Therapy: Analysis of Prescription Profiles in Non-Comorbid Inpatients to Enhance Treatment Strategies and Clinical Outcomes - Fendy Prasetyawan; Yuneka Saristiana; Faisal Akhmal Muslikh; Ratna Mildawati; Ilhawa Zahra (Journal Health of Indonesian, 2023)
This study explores the clinical characteristics, treatment patterns, and outcomes of COVID-19 inpatients without comorbidities, aiming to contribute valuable insights to the management of the disease. Through meticulous data collection from medical records of 468 confirmed COVID-19 patients admitted to Gambiran Regional General Hospital between April and June 2020, 36 patients meeting inclusion criteria were identified. The research findings reveal a higher incidence of COVID-19 among males and a prevalent age group of 31-40 years. Notably, elderly individuals and those with underlying health conditions face a greater risk of severe outcomes, underscoring the importance of tailored interventions for vulnerable populations. The study highlights a diverse treatment approach, with a significant proportion of patients receiving supplements to bolster immune function. Antiviral medications like Favipiravir are also utilized to inhibit viral replication, although definitive treatment for COVID-19 remains elusive. Antibiotics play a crucial role in preventing bacterial respiratory infections, while supportive medications help alleviate symptoms commonly associated with the disease. Importantly, the findings emphasize the multifaceted nature of COVID-19 management and the need for targeted interventions to optimize patient outcomes. By elucidating the therapeutic landscape and clinical course of COVID-19 inpatients without comorbidities, this study contributes to the growing body of knowledge surrounding the disease. These insights can inform clinical decision-making, resource allocation, and public health strategies aimed at combating the ongoing pandemic.